2013
DOI: 10.1038/cr.2013.173
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing reveals the disruption of methylation of imprinted gene in induced pluripotent stem cells

Abstract: It remains controversial whether the abnormal epigenetic modifications accumulated in the induced pluripotent stem cells (iPSCs) can ultimately affect iPSC pluripotency. To probe this question, iPSC lines with the same genetic background and proviral integration sites were established, and the pluripotency state of each iPSC line was characterized using tetraploid (4N) complementation assay. Subsequently, gene expression and global epigenetic modifications of "4N-ON" and the corresponding "4N-OFF" iPSC lines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 41 publications
4
59
0
Order By: Relevance
“…Interestingly, c-Myc, which is a key gene known to significantly impact TGF-b signaling, was expressed at a higher level in hematopoietic cells than in fibroblasts, as shown by our own RNA-seq data ( Supplementary Fig. S9) and an independent public dataset (GSE36290) [28]. This result is supportive of earlier findings in which a TGF-b inhibitor much more significantly promoted reprogramming in the absence than in the presence of c-Myc [25,26].…”
Section: Fig 2 Expression Profile Analysis Of Early Reprogramming Osupporting
confidence: 81%
“…Interestingly, c-Myc, which is a key gene known to significantly impact TGF-b signaling, was expressed at a higher level in hematopoietic cells than in fibroblasts, as shown by our own RNA-seq data ( Supplementary Fig. S9) and an independent public dataset (GSE36290) [28]. This result is supportive of earlier findings in which a TGF-b inhibitor much more significantly promoted reprogramming in the absence than in the presence of c-Myc [25,26].…”
Section: Fig 2 Expression Profile Analysis Of Early Reprogramming Osupporting
confidence: 81%
“…2). Moreover, in a recent study, we have demonstrated that the core histone modifications (H3K4me2, H3K4me3, H3K27me3) are comparable among iPSC lines that can produce all-iPSC mice 24 . Taken together, we conclude that although alliPSC mice can be produced up to six generations, their viability decreases with increasing generations, and epigenetic effects might not be a major cause of this reduction in viability.…”
Section: Resultsmentioning
confidence: 99%
“…MeDIP-seq and RNA-seq of all eight sequential iPSC lines were conducted as previously described 24 . In brief, the genomic DNA was sonicated to 100-500 bp and adaptor was then ligated to the end of the DNA fragments according to the paired-end DNA sample prep kit (Illumina).…”
Section: Generation Of Ipscsmentioning
confidence: 99%
“…ESC small-RNA-Seq data were derived from the study of Chang et al 36 (GSM886478). Following pre-processing, adapter-trimmed reads were aligned against known human mature miRNA sequences (miRBase v20 (ref.…”
Section: Methodsmentioning
confidence: 99%